Greening Growth in Pakistan through Transport Sector Reforms : Strategic Environmental, Poverty, and Social Assessment - Sánchez-Triana, Ernesto; Afzal, Javaid; Biller, Dan; Malik, Sohail (Washington, DC: World Bank, 2013)
The Government of Pakistan's (GoP's) 2011 Framework for Economic Growth seeks to place Pakistan on a sustained high economic growth path of 7 percent per year through measures to reduce the cost of doing business, improve the investment climate, and strengthen institutions. Trade and transport reforms are central to achieve the Framework's goals. The transport sector constitutes 10 percent of Pakistan's Gross Domestic Product (GDP) and provides 6 percent of the employment in the country. The sector plays an important role in linking other sectors in the economy, contributes to both domestic and international trade, and helps facilitate the spatial transformation occurring in Pakistan. The present patterns in transport and trade logistics generate inefficiencies that are costing Pakistan's economy roughly 4-6 percent of GDP per year, which is a major constraint on the aspirations set out in the Framework. This report examines the poverty, social, and environmental aspects associated with trade and transport sector reforms aimed at increasing the freight transport sector's productivity to meet the Framework's goals. This report is organized as follows. Chapter 1 provides the objectives and methodology of this work. Chapter 2 discusses the sector status and the trade and transport policy reforms. Chapter 3 establishes the priority issues associated with freight transport reform. Chapters 4 and 5 focused on the social and environmental aspects of the reform, respectively. And chapters 6 and 7 conclude the report by discussing policy options to promote environmentally and socially sustainable trade and transport and an agenda to advance environmentally and socially sustainable trade and transport reforms in Pakistan.